Evaluation of Efficacy, Safety, and Tolerability of Brivaracetam as Adjunctive Therapy in the Treatment of Focal Seizures: An Analysis of Mexican Patients (Revista de Medicina Clinica, 2025)
Introduction: To evaluate, in a post-hoc subgroup analysis, the efficacy, safety, and tolerability of brivaracetam (BRV) as an adjunctive treatment compared with placebo in patients with uncontrolled focal (partial-onset) seizures recruited in Mexico. Patients and Methods: Seizure outcomes data were pooled from two phase III trials, NCT01339559 (N01379) and NCT00150800 (N01199). The pooled safety and efficacy data from these trials for the Mexican population were evaluated as a descriptive analysis of these core trials. Results: Of 179 Mexican patients who were evaluated, 67.5% completed the two trials, including a long-term follow-up that lasted more than 4 years. Of the patients who completed, 27 (96.3%) had been treated with a BRV dose of 20 mg/day, 26 (88.5%) with 50 mg/day, 21 (81.0%) with 100 mg/day, and 21 (85.7%) with 200 mg/day. After 2 years’ treatment, 81% of patients had responded to treatment at a dose > 50 mg/day. In the safety analysis, only five patients discontinued because of treatment, and 26 patients had developed serious adverse events overall in the two trials. Conclusion: Adjunctive treatment with BRV in adults with focal seizures was effective and generally well tolerated when administered long term.
Keywords: Brivaracetam; Adjunctive therapy; Focal seizure; Epilepsy; Mexico